2018
DOI: 10.6018/analesps.34.2.295331
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from Positive and Negative Affect to Depressive Symptoms: Multiple Mediation of Emotion Regulation Strategies

Abstract: The current study aims to examine the multiple mediations of emotion regulation strategies in the relationship between positive and negative affect and depressive symptoms in adolescents. Participants included 290 students attending middle schools in a mid-size city in Southeastern Anatolian region. Among students, 137 were females (47.2%) and 153 (52.8%) were males. Participants’ ages ranged between 9 and 15 with a mean of 12.12, <em>SD</em>=1.53. Research data were collected through Positive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Affective experiences, especially negative affectivity, were found as the significant of whether the individual’s impact of the adverse childhood experiences was scored as negative (LaNoue et al, 2013). Consistent with the current outcomes, literature has suggested that positive affective experiences mitigate the negative impacts of adverse experiences on adolescents’ functional and mental health outcomes (Arslan, 2018c; Jennissen et al, 2016; Kansky & Diener, 2017; Moore & Diener, 2019; Pressman & Cohen, 2005; Yildiz & Kızıldağ, 2018), and positive affectivity may influence their use of resources and mechanism in coping process with psychological maltreatment and social ostracism. Further, given the mediating role of negative affectivity, adolescents with high levels of negative affectivity may be reflecting the impacts of maltreatment experiences on their current health and functioning (LaNoue et al, 2013), and; thereby, they may experience more psychosocial adjustment difficulties, such as loneliness.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Affective experiences, especially negative affectivity, were found as the significant of whether the individual’s impact of the adverse childhood experiences was scored as negative (LaNoue et al, 2013). Consistent with the current outcomes, literature has suggested that positive affective experiences mitigate the negative impacts of adverse experiences on adolescents’ functional and mental health outcomes (Arslan, 2018c; Jennissen et al, 2016; Kansky & Diener, 2017; Moore & Diener, 2019; Pressman & Cohen, 2005; Yildiz & Kızıldağ, 2018), and positive affectivity may influence their use of resources and mechanism in coping process with psychological maltreatment and social ostracism. Further, given the mediating role of negative affectivity, adolescents with high levels of negative affectivity may be reflecting the impacts of maltreatment experiences on their current health and functioning (LaNoue et al, 2013), and; thereby, they may experience more psychosocial adjustment difficulties, such as loneliness.…”
Section: Discussionsupporting
confidence: 72%
“…Further, given the mediating role of negative affectivity, adolescents with high levels of negative affectivity may be reflecting the impacts of maltreatment experiences on their current health and functioning (LaNoue et al, 2013), and; thereby, they may experience more psychosocial adjustment difficulties, such as loneliness. Several research provides evidence supporting the role of affective experience on a variety of health and adjustment outcomes (Arslan, 2018c; Kansky & Diener, 2017; Moore & Diener, 2019; Yildiz & Kızıldağ, 2018). Jennissen et al (2016) for example reported that negative affective experience mediated the association of maltreatment with emotional dysregulation and psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…The Cronbach α reliability of this aggregate scale was 0.68, and composite reliability (CR) was 0.69 in the present study. Past studies utilizing this scale show CR values in the 0.72–0.87 (Mazefsky et al, 2021; Yildiz & Kızıldağ, 2018).…”
Section: Methodsmentioning
confidence: 94%
“…However, contrary to our hypothesis, no association between positive ER style and depressive symptoms was found, perhaps because there are other factors (e.g., family, cultural, and personal) involved in this relationship. For example, as indicated by Yildiz and Kizildağ [ 27 ], an adolescent with certain family and social conditions may exhibit depressive symptoms, even though he or she is employing positive ER strategies to cope with feelings about academic failure. Surprisingly, also against our expectations, a low positive association between positive ER style and anxiety symptoms was found.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism most frequently highlighted as a mediator or moderator of the relationship between temperamental factors (e.g., NA and PA) and the presence of depressive and anxiety symptoms is the regulation of emotions. For example, recent studies on this topic have stated that some styles of ER, labeled as poor or negative, mediate the relationship between both NA and PA and depression [ 27 ], and between NA and anxiety [ 28 ]. In addition, a moderating role of ER has been shown in the relationship between NA and depressive symptomatology [ 29 ].…”
Section: Introductionmentioning
confidence: 99%